(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The basic purpose of this paper is to present, analyse and assess Train to Pakistan as Khushwant Singh’s literary achievement. Khushwant Singh is one of India’s recognized men of letters with a universal notoriety. A brief record of his accomplishment as an author, short-story essayist, student of history, writer, sketchiest, columnist is sufficiently adequate to set up him Indian Writing in English as an adaptable virtuoso. He has created two books, a significant number of short stories, a legitimate history of the Skihs, life stories of Sikh pioneers and many articles which uncover his idea and sentiment an extraordinary author. His presentation of the genuine and the comic makes him remain as a column and associate among current Indian scholars on subjects of worry to contemporary man.